Isolation and Fermentation of Lactobacillus plantarum JR64 as an Omega 6 Probiotic Producer - Lanjar Sumarno; Djumali Mangunwidjaja; Anas M. Fauzi; Khaswar Syamsu; Nastiti Siswi Indrasti; Bambang Prasetya (Chemical Engineering Diponegoro University, 2011)
Application of lactic acid probiotic bacteria in health food diversification currently is progressing rapidly. It is encouraged the study of searching the potential strains from local resources (Ponorogo Residence) namely noni fruits (badeg pace) and noni wine. Aims of this study were to perform the isolation, identification, and production of probiotic Lactobacillus sp. JR64 fermentation process as a producer of Omega-6 (ω-6) lowering cholesterol and design of probiotic creamy product. Beginning stages of research was strains isolating and in-vitro testing, the best result were used in molecular identification technology development for the production of metabolites through the manipulation of environmental variation of glucose 20 g / l, 30 g / l and 40 g / l that influenced the substrate concentration of linoleic acid productivity. The result of new isolates isolation showed that isolates that obtained from noni wine, Lactobacillus plantarum JR64, was potential as probiotic condidate. The effieciency of fermentation substrates using Yx/s and Yp /s in the exponential phase was the highest value for the fermentation of 24 hours of Yx/ s; 17.03% and Y p/s; 74.72%, while the results of design and the best formulation for viability cells of lactobacillus plantarum probiotics JR64 was composed of 15 g and 50g butter 15 g icing sugar as well as during storage of the refrigerant temperature was 8.92 x 108 CFU / ml. [Key Words : Omega-6, Lactobacillus plantarum JR64, fermentation]